2006
DOI: 10.1681/asn.2006091030
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3–Triggered Antimicrobial Response—Another Pleiotropic Effect beyond Mineral and Bone Metabolism

Abstract: N iels Ryberg Finsen, who received the third Nobel prize in medicine in 1903, was honored because in 1895 he had discovered a cure for a disease that had been incurable before, i.e., skin tuberculosis known as lupus vulgaris (1-3). Phototherapy was performed by exposing the skin to an electrical arc lamp and producing moderate sunburn. Although alternative or complementary mechanisms have been proposed, such as generation of singlet oxygen by the porphyrin molecules in Mycobacterium tuberculosis, it appears th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This was followed by subsequent description of 'non-classical functions of vitamin D', which include immunomodulatory properties of vitamin D, firmly supported by numerous in vitro and animal experiments (Bouillon et al, 2008). The in vitro findings consistently suggest that vitamin D enhances antimicrobial activity at early stages of infection (Liu et al, 2006;Urry et al, 2009) and provides negative feedback at later stages (Sadeghi et al, 2006). The inhibitory effects of vitamin D on adaptive immune response include induction of the potent antiinflammatory cytokine IL-10.…”
Section: Introductionmentioning
confidence: 93%
“…This was followed by subsequent description of 'non-classical functions of vitamin D', which include immunomodulatory properties of vitamin D, firmly supported by numerous in vitro and animal experiments (Bouillon et al, 2008). The in vitro findings consistently suggest that vitamin D enhances antimicrobial activity at early stages of infection (Liu et al, 2006;Urry et al, 2009) and provides negative feedback at later stages (Sadeghi et al, 2006). The inhibitory effects of vitamin D on adaptive immune response include induction of the potent antiinflammatory cytokine IL-10.…”
Section: Introductionmentioning
confidence: 93%
“…In DCs localized production of 1,25(OH) 2 D 3 may affect proliferation and phenotype of adjacent T-cells but it is also able to exert autocrine effects by suppressing DC maturation and maintaining these cells in a more tolerogenic state [27]. Like DCs, macrophages are also able to present antigen and influence acquired immune responses but we have recently shown that the most likely function of 1␣-hydroxylase in these cells is to stimulate innate immunity [29]. In this study expression of 1␣-OHase by monocytes was induced as a result of ligand binding to TLR2 but the enzyme was only functional if sufficient substrate (25OHD 3 ) was available for conversion to 1,25(OH) 2 D 3 .…”
Section: Functional Impact Of Extra-renal 125(oh) 2 D 3 Productionmentioning
confidence: 99%
“…Instead, there are numerous reports showing the potential of VD to inhibit microorganism proliferation [15][16][17][18][19][20], particularly in the case of tuberculosis and other mycobacterial infections [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%